2014
DOI: 10.1002/hep.26695
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis contributes to fibrogenesis in the course of chronic liver injury in mice

Abstract: Nonalcoholic fatty liver disease (NAFLD) may lead to hepatic fibrosis. Dietary habits affect gut microbiota composition, whereas endotoxins produced by Gram‐negative bacteria stimulate hepatic fibrogenesis. However, the mechanisms of action and the potential effect of microbiota in the liver are still unknown. Thus, we sought to analyze whether microbiota may interfere with liver fibrogenesis. Mice fed control (CTRL) or high‐fat diet (HFD) were subjected to either bile duct ligation (BDL) or CCl4 treatment. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
182
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(199 citation statements)
references
References 38 publications
8
182
0
1
Order By: Relevance
“…As expected, in our murine model of NAFLD metagenomic studies revealed differences at phylum, class and genus levels between HFD-fed mice and controls, leading to dysbiosis. As previously described, HFD-induced dysbiosis was characterized by an increase in Gram-negative bacteria and, most important, by a general decrease of total bacteria concentration [40]. In turn, it has been described that differences in gut microbial composition can determine response to HFD in mice [29,41], which would explain the wide spectrum of NAFLD observed in our study in accordance with the individual metabolic phenotype, as corroborated by results obtained from correlation analysis.…”
Section: Discussionsupporting
confidence: 90%
“…As expected, in our murine model of NAFLD metagenomic studies revealed differences at phylum, class and genus levels between HFD-fed mice and controls, leading to dysbiosis. As previously described, HFD-induced dysbiosis was characterized by an increase in Gram-negative bacteria and, most important, by a general decrease of total bacteria concentration [40]. In turn, it has been described that differences in gut microbial composition can determine response to HFD in mice [29,41], which would explain the wide spectrum of NAFLD observed in our study in accordance with the individual metabolic phenotype, as corroborated by results obtained from correlation analysis.…”
Section: Discussionsupporting
confidence: 90%
“…Gut dysbiosis has been linked with endotoxin-mediated chronic disease in mouse models [51,52]. Sphingosine, a hydrolytic product of dietary SM, is known to have bactericidal effects [53].…”
Section: Discussionmentioning
confidence: 99%
“…For example, microbiota effects upon body weight, adiposity, lipid metabolism, liver disease, intestinal mucosal function, colon carcinogenesis, and cardiovascular function have recently been linked to luminal bile acid metabolism and modulation of bile acid signaling ( 26, 213-218 ). Of note, these studies are at the forefront of a new fi eld, and make innovative use of mouse models with altered microbiomes, including models that are germ-free or colonized with specifi c organisms, including microbiota from humans with select clinical characteristics ( 214,216,(219)(220)(221)(222)(223)(224). Compared with mice raised conventionally, the pool of bile acids in germ-free mice is less "FXR agonistic," because the bile and luminal contents include an increased proportion of tauro-␤ -murocholic acid, an endogenous mouse bile acid species that functions as an FXR antagonist ( 26, 223 ).…”
Section: Consequences Of Intestinal Bile Acid Metabolism On Bile Acidmentioning
confidence: 99%